The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1099/ijs.0.044057-0
|View full text |Cite
|
Sign up to set email alerts
|

Sphingopyxis rigui sp. nov. and Sphingopyxis wooponensis sp. nov., isolated from wetland freshwater, and emended description of the genus Sphingopyxis

Abstract: Two yellow-pigmented, Gram-reaction-negative strains, designated 01SU5-P T and 03SU3-P T , were isolated from the freshwater of Woopo wetland, Republic of Korea. Both strains were aerobic, non-motile and catalase-negative. Phylogenetic analysis based on 16S rRNA gene sequences indicated that the two isolates belong to the genus Sphingopyxis, showing the highest level of sequence similarity with respect to Sphingopyxis witflariensis W-50 T (95.4-95.7 %). The two novel isolates shared 99.4 % sequence similarity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…As referred in Table S8, the significant presence of PAHdegrading bacteria like Comamonas (Goyal and Zylstra 1996) and Diaphorobacter (Klankeo et al 2009) indicated the removal of corresponding pollutants in aerobic sludge leading to detoxification of CWW (Zhang et al 2013). The high abundances of NHC-degrading bacteria Brevundimonas, Sphingopyxis, Sphingosinicella Stolz 2009;Baik et al 2013), and Comamonas (Felföldi et al 2010;Zhang et al 2015) also tallied with the complete disappearance of NHCs in the final effluent in this study. The NHCutilizing bacteria detected in CWW treating sludge exhibit considerable potential for biotechnological applications.…”
Section: Discussionmentioning
confidence: 92%
“…As referred in Table S8, the significant presence of PAHdegrading bacteria like Comamonas (Goyal and Zylstra 1996) and Diaphorobacter (Klankeo et al 2009) indicated the removal of corresponding pollutants in aerobic sludge leading to detoxification of CWW (Zhang et al 2013). The high abundances of NHC-degrading bacteria Brevundimonas, Sphingopyxis, Sphingosinicella Stolz 2009;Baik et al 2013), and Comamonas (Felföldi et al 2010;Zhang et al 2015) also tallied with the complete disappearance of NHCs in the final effluent in this study. The NHCutilizing bacteria detected in CWW treating sludge exhibit considerable potential for biotechnological applications.…”
Section: Discussionmentioning
confidence: 92%
“…This threshold has been reasonably increased to between 98.2 and 99.0% depending on the taxonomic group which is to be investigated (Meier-Kolthoff et al 2013;Stackebrandt and Ebers 2006). Therefore, DNA-DNA hybridisation experiments were performed between strain TA-C7e T and three closely related species of the genus Massilia according to the methods of Baik et al (2013). DNA-DNA hybridisation was carried out by the membrane filter technique using the DIG High Prime DNA Labeling and Detection Starter Kit II (Roche Applied Science).…”
Section: Chemotaxonomic Characterisationmentioning
confidence: 99%
“…Strains IMCC1753 T and IMCC26285 T contained PE, PME, PC, PG, DPG and SGL as major polar lipids (Fig. S3), similar to major polar lipids of Sphingorhabdus [9,12,[15][16][17]. The major polyamine and polar lipids of both strains were highly similar except for the presence of an unidentified glycolipid and an unidentified lipid in strain IMCC26285 T .…”
Section: Phenotypic and Chemotaxonomic Characterizationmentioning
confidence: 73%
“…Polar lipids were extracted according to the procedures described by Minnikin [17]. †Data from Baik et al [16]. ‡Data from Jogler et al [9].…”
Section: Phenotypic and Chemotaxonomic Characterizationmentioning
confidence: 99%
See 1 more Smart Citation